An economic evaluation of Levofloxacin versus Cefuroxime Axetil in the outpatient treatment of adults with community-acquired pneumonia - Rittenhouse, Brian E.; Stinnett, Aaron.A.; Dulisse, Brian; Henke, Curtis.J.; Potter, Lori; Balakrishnan Parasuraman; Martens, Leon L.; Williams, R. Rex; Kojak, Claire (2000)
Objective: To examine treatment costs of community-acquired pneumonia (CAP) in adult outpatients given oral (po) levofloxacin or cefuroxime axetil as initial therapy.